This time is really different: The multiplier effect of the Paycheck Protection Program (PPP) on small business bank loans - Karakaplan, Mustafa U. (Journal of Banking & Finance, 2021)
In response to the COVID-19 crisis, the U.S. government passed the Coronavirus Aid, Relief, and Economic Security (CARES) Act on March 27, 2020, creating the Paycheck Protection Program (PPP), among others, to aid small businesses and their employees. Most PPP loans were administered by commercial banks in return for fees, and the banks bore little monitoring costs or risks, since PPP loans were forgivable by the government. I analyze if PPP loans of up to 1 million were net substitutes or complements for conventional small business loans of the same size for the PPP-issuing banks. The 1 million upper bound roughly corresponds to credits to the smallest firms that are often financially constrained. Using Call Report data through 2020:Q4, I find significant net complementarities. An additional dollar of PPP credit of up to $1 million had multiplier effects on conventional loans to the smallest firms of about an extra dollar.